Elucidation of the technological conditions for the formation of alkali silicates heat-insulating products based on ash-removal of thermal power plants and liquid glass - Dryuchko, Оleksandr; Bunyakina , Natalia; Halai, Vasyl; Boriak, Bohdan; Tretiak , Andrii; Kyslytsia, Dmytro (Academic journal Industrial Machine Building Civil Engineering, 2024)
The raw material mixture from the silicon-like techno genic component the ash-removal of thermal power plants and the preparation methods of waterproof porous heat-insulated materials wide usage for raw mass hot foaming powdered two-stage technology are developed. The development uses the polyfunctional properties of liquid glass as a) the binder component; c) breeder; c) the speed regulator of the clamping mass hardening. Its optimized version begins to solidify at its usual temperature from the moment its "reproduction" is soluble glass and forms a paste-shaped cake with a set of properties necessary for the next fragmentation. The proposed formulation allows compositions processing in various ways, with the formation of granular heat-insulating fillers, materials for thermal insulation in complex structures, slab and shell-like types of thermal insulation materials. The task is set, depending on the goals and features of the tasks being solved; it is possible to conduct several different methods at the final stages of their obtaining. Two stages of the recycling process determine the character and behavior of the rare-glass composite systems constituent components during heat treatment, their strong adhesion to most structural materials and the need to solve billets easy removal problem from the molding unit. Study results can be used in the field of building materials production, in particular porous artificial products, in obtaining granular insulating material and light aggregate for concrete industrial and civil construction, in thermal engineering as thermal insulation, etc.
Keywords: alkaline-silicate heat-insulation composite materials; ash removal; liquid glass; thermal foaming